Chinese Maritime Politics in the 13th Century, Malay States and Javanese Imperium - Hakam, Saiful (Universitas Islam Negeri Raden Mas Said Surakarta, 2017)
This study aims to explain about the rise of the Chinese trading culture, which is considered original at first then change progressively based on the internal process, and become damaged after making contacts with the native civilizations, is completely dissatisfying, though part of the truth is explained. Based on the critical analysis approach from the historical facts written by some scholars, the result of this study shows that the political and cultural changes were absolutely a sign of remarkable shock. Mongol conquests were contributed to these changes, though indirectly. Indian civilization was accepted by the native people, which then also influenced by the native culture. While the Islamic Nuance in Indian Ocean had been colored by Islamic nuance for approximately two centuries, wherein the trades in the middle and Chinese oceans were united naturally. Meanwhile Southeast Asia had grown rapidly after being involved in the hectic trading traffic. There were new social groups with the wealth of mobile capital, with a new spirit as the trades, in which in its development, there was a new form of state which was called as sultanate. One of the most important facts of that period is the rise of Java as a great sea power.